ANALISIS KEMAMPUAN MULTIREPRESENTASI PESERTA DIDIK DALAM MENGERJAKAN SOAL GERAK LURUS BERUBAH BERATURAN DI SMA - Bagas Eko Prakoso; Tomo Djudin; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThis research aimed to determine the students multi-representation ability in working on questions about Accelerated Linear Motion in State Senior High School 7 in Pontianak. This study untilized a survey method involving 130 10th grade students from the school. The research test was in the form of 10 questions regarding multi-representation as well as 10 test to measure learning outcomes. The average percentage of multi-representation abilities of students was included in the “medium” category by a rate of 62,22%. The capability of students multi-representation to compose mathematic representation with percentage 93,68% and the lowest capability of students multi-representation from sketch representation with percentage 23,16%. Furthermore, there were differences in multi-representation abilities based on gender which were confirmed from the Mann-whitney test result (P<0,05) with the result of analysis showing that female students are superior in all types of representation than male students. This investigation also found that there was correlation of multi-representation ability of students in working on the problem with students learning outcomes which was shown from the results of the Product Moment Correlation Test (Rcount 0,573>Rtable 0,213), so learning involving multi-representation demanded to improve learning outcomes in physics. Future studies are expected to be able to develop physics learning strategies to enhance multi-representation capabilities and student learning outcomes. Keywords: Gender, Learning Outcomes, Multi-representation Ability